Respuesta :

Answers:

Question 51.  [tex]\boldsymbol{(x-3)^2 + (y-1)^2 = 4}[/tex]

Question 52.  [tex]\boldsymbol{(x+3)^2 + (y-2)^2 = 4}[/tex]

============================================================

Explanation:

The template of any circle is

[tex](x-h)^2 + (y-k)^2 = r^2[/tex]

with (h,k) being the center and r as the radius

For question 51, the center is (3, 1) and the radius is 2. So,

[tex](x-h)^2 + (y-k)^2 = r^2\\\\(x-3)^2 + (y-1)^2 = 2^2\\\\(x-3)^2 + (y-1)^2 = 4[/tex]

Question 52 will have similar steps. This time the center is (-3, 2) and the radius is 2.

#51

Centre (3,1)

Radius=2

Equation

  • (x-h)²+(y-k)²+r²
  • (x-3)²+(y-1)²=2²
  • (x-3)²+(y-1)²=4

#52

centre(-3,2)

radius=2

Equation

  • (x+3)²+(y-2)²=4